Termitomyces assamicus (Lyophyllaceae)—A new species of Termitomyces from India - Das, Lakshmi Rupa; Chattopadhyay, Pinaki; Dutta, Arun Kumar; Narzary, Diganta; Rana, Tikam S. (Phytotaxa, 2023)
Based on morphological and molecular phylogenetic analysis (ITS-rDNA sequence), a new species, Termitomyces assamicus, is described after the Indian state of Assam. Termitomyces assamicus is characterized by a medium-sized pileus, brownish orange to grey or greyish red with a conical, pointed perforatorium; white to pale grey lamellae with a serrated edge; an orange grey to greyish orange stipe measuring 50–100 mm long; absence of annulus; greyish brown to yellowish brown pseudorhiza measuring 70–100 mm long; ellipsoid basidiospores with a mean of 8.3 × 5.0 μm; clavate cheilocystidia measuring 21–36 × 8–16 µm; and broadly clavate to pyriform pleurocystidia (23–32 × 12–23 µm). The new species was compared with closely related taxa using morpho-molecular data. A detailed morphological description with field images, micromorphology illustration, and a phylogenetic tree to show the position of the new species are also provided.